2014
DOI: 10.1186/1758-5996-6-74
|View full text |Cite
|
Sign up to set email alerts
|

A standard ballroom and Latin dance program to improve fitness and adherence to physical activity in individuals with type 2 diabetes and in obesity

Abstract: ObjectiveTo test the effectiveness of a dance program to improve fitness and adherence to physical activity in subjects with type 2 diabetes and obesity.Research Design and MethodsFollowing a motivational interviewing session, 100 subjects with diabetes and/or obesity were enrolled either in a dance program (DP, n = 42) or in a self-selected physical activity program (SSP, n = 58), according to their preferences. Outcome measures were reduced BMI/waist circumference, improved metabolic control in type 2 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 40 publications
(50 reference statements)
1
34
0
Order By: Relevance
“…In Italy, Mangeri and colleagues had middle- and older-aged adults with diabetes and/or obesity enroll in either a dance program or in a self-selected PA program. Both programs significantly decreased body composition at 3 months and 6 months (Mangeri, Montesi, Forlani, Grave, & Marchesini, 2014), but participants were not randomized into study conditions, and cognition was not assessed. Recent evidence suggests that Latin partnered social dance to salsa music is of moderate to vigorous PA intensity, and promotes interest, enjoyment, and a positive psychological outlook among novice to advanced adult Latin dancers (Domene, Moir, Pummell, & Easton, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, Mangeri and colleagues had middle- and older-aged adults with diabetes and/or obesity enroll in either a dance program or in a self-selected PA program. Both programs significantly decreased body composition at 3 months and 6 months (Mangeri, Montesi, Forlani, Grave, & Marchesini, 2014), but participants were not randomized into study conditions, and cognition was not assessed. Recent evidence suggests that Latin partnered social dance to salsa music is of moderate to vigorous PA intensity, and promotes interest, enjoyment, and a positive psychological outlook among novice to advanced adult Latin dancers (Domene, Moir, Pummell, & Easton, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Physical function was measured using the six-minute walk test (6MWT) (Guyatt et al, 1985) a common field test shown to be reliable, valid, and safe in adults (including elderly adults) with a variety of medical conditions, including diabetes (Alfonso-Rosa, Del Pozo-Cruz, Del Pozo-Cruz, Sanudo, & Rogers, 2014; Dunbar et al, 2015; Ekman, Klintenberg, Bjorck, Norstrom, & Ridderstrale, 2013; Enright, 2003; Enright et al, 2003; Mangeri, Montesi, Forlani, Dalle Grave, & Marchesini, 2014; Pariser, Ann Demeuro, Gillette, & Stephen, 2010). The 6MWD has been shown to reflect the capacity for usual daily activities (Zeballos & Weisman, 2002) and walking ability (Ekman et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Our SE program was designed to adhere to current intensity recommendations for exercise (10), whereas our BD program was a group fitness class that made it challenging to assign individual HR intensities. It is not unusual in social fitness classes for exercise to be performed at a higher intensity because of the lack of awareness of the discomfort of exercise (23). When comparing the intensity of the BD and SE programs, it is likely that the intensity achieved during BD was greater, as reflected in the significant improvement in aerobic fitness in the BD but not in the SE group.…”
Section: Discussionmentioning
confidence: 88%
“…However, despite the consistent protocol, the attendance at the BD program was higher (78%) than the SE program (67%). Dance interventions (23,33), specifically BD, have shown excellent adherence when offered as an exercise program because of their perceived improved energy levels, decreased stress, and enjoyable social environment (23,33). In personal statements from the BD participants, we received similar feedback indicating their enjoyment of the BD program for its social aspect and fun atmosphere.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation